REPRESENTASI POLITIK PEREMPUAN DALAM PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA KOTA TOMOHON - Gicheel Aurelia Theresa Lenzun; Daisy Posumah; Trilke Erita Tulung; Johnly Roycke Pangemanan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to identify and explore how female voters in Tomohon City interpret women's political representation in the Mayoral and Vice-Mayoral elections. Women's representation in politics has become a crucial issue as it relates to the fulfillment of political rights and the quality of local democracy. This research employs a qualitative approach with a phenomenological research type to delve into the deep experiences and perspectives of informants, with data collection techniques conducted through in-depth interviews. The results of the study indicate that the presence of women in the political contestation of Tomohon City is interpreted by female voters as a symbol of courage, authority, and moral quality. However, there is a shift in the expectations of female voters, where they desire female leaders who are stronger, more vocal, and substantive in the future. These findings emphasize that gender is no longer the sole determinant or guarantee of victory in politics; rather, evidence of real performance has become the primary consideration for female voters.